2010
DOI: 10.1016/j.ejcts.2009.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Economic aspects of deep sternal wound infections☆

Abstract: DSWI represents an important economic factor for the hospital as they may almost triple the costs for patients undergoing CABG. Thus, appropriate infection control measures for the prevention of DSWI should be enforced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
129
0
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(140 citation statements)
references
References 14 publications
3
129
0
7
Order By: Relevance
“…Furthermore, Cabbabe et al 16) found patients undergoing one step radical debridement with muscle flap coverage had significantly shorter hospital stay and lower mortality compared to patients with DSWI who were referred to flap coverage after undergoing extended management by the thoracic surgeons. With the substantial increased cost of care for patients with DSWI, 22) interdisciplinary teamwork regarding the possibility of a flap reconstruction should, in our opinion, be conducted at an early stage after the DSWI diagnosis. The in-hospital mortality rate for patients undergoing flap reconstruction in our study was 7.4% (n = 4), which is a little higher than the 2.7%-5.4% mortality rate reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Cabbabe et al 16) found patients undergoing one step radical debridement with muscle flap coverage had significantly shorter hospital stay and lower mortality compared to patients with DSWI who were referred to flap coverage after undergoing extended management by the thoracic surgeons. With the substantial increased cost of care for patients with DSWI, 22) interdisciplinary teamwork regarding the possibility of a flap reconstruction should, in our opinion, be conducted at an early stage after the DSWI diagnosis. The in-hospital mortality rate for patients undergoing flap reconstruction in our study was 7.4% (n = 4), which is a little higher than the 2.7%-5.4% mortality rate reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the occurrence of mediastinitis exerts a negative impact on the ensuing survival of patients and on hospital costs 4 .…”
Section: Mediastinitis Is a Deep Sternal Wound Infectionmentioning
confidence: 99%
“…In a 10-year follow-up study after coronary artery bypass grafting, the adjusted survival rate was 39% for patients who developed DSWI compared with 70% in patients who did not [14] . Excess costs arise primarily owing to additional antibiotic treatments and surgical procedures, as well as increased hospital length of stay [13,15] . The management of DSWI has progressed through long-lasting clinical experience.…”
Section: Introductionmentioning
confidence: 99%
“…Despite many advances in prevention, it still remains significant and ranges between 0.5% and 6.8% [6][7][8][9][10] , with in-hospital mortality rates between 7% and 35% [2,3,7,9,[11][12][13] . Moreover, mid-and long-term survival is significantly reduced in patients that have experienced DSWI.…”
Section: Introductionmentioning
confidence: 99%